Nullity of the reform of article 133 of the Senate Standing Orders, which gave granted the Senate bureau exclusive authority to decide on the application of the urgent procedure in the case of private members’ bills. Concerning the action of unconstitutionality num. 7998-2023 (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2025)
The judgement rules on the unconstitutionality of the reform of the Senate Standing Orders relating to the urgent legislative procedure consisting on the granting of the power to decide whether or not to apply the urgent procedure to private members’ bills to the Senate.
Keywords: urgent legislative procedure; Senate Standing Orders; Government bills; private members’ bills